2021
DOI: 10.1108/intr-10-2019-0439
|View full text |Cite
|
Sign up to set email alerts
|

Laziness as an explanation for the privacy paradox: a longitudinal empirical investigation

Abstract: Purpose“Smart devices think you're “too lazy” to opt out of privacy defaults” was the headline of a recent news report indicating that individuals might be too lazy to stop disclosing their private information and therefore to protect their information privacy. In current privacy research, privacy concerns and self-disclosure are central constructs regarding protecting privacy. One might assume that being concerned about protecting privacy would lead individuals to disclose less personal information. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 101 publications
(163 reference statements)
0
8
0
1
Order By: Relevance
“…The study by Wirth et al [68] examines the extent to which individual laziness affects privacy. The results showed that individuals who are predominantly lazy are more likely to disclose their data as well as not change their privacy settings, despite the fact that changes were made to data practices.…”
Section: Related Workmentioning
confidence: 99%
“…The study by Wirth et al [68] examines the extent to which individual laziness affects privacy. The results showed that individuals who are predominantly lazy are more likely to disclose their data as well as not change their privacy settings, despite the fact that changes were made to data practices.…”
Section: Related Workmentioning
confidence: 99%
“…Thus, the potential benefits of the engagement may outweigh users' privacy concerns when conducting a costbenefit analysis, which may lead them to play an active role in online communities (Debatin et al, 2009). Furthermore, personal traits may serve as a moderator when users assess the privacy threats and engagement benefits (Aivazpour and Rao, 2020;Wirth et al, 2021).…”
Section: Health Information Privacy Concerns and Online Engagementmentioning
confidence: 99%
“…Other factors such as perceptions of privacy risk may prove insightful to unpacking both privacy resignation and disempowerment, as the potential effects of resignation on the privacy calculus are teased out (e.g. Meier and Krämer, 2022; Wirth et al, 2018). In addition, it is important to note that overlapping conceptualizations of privacy can occupy the same socio-technical space, as is often evident in social media where individuals simultaneously engage in both vertical and horizontal privacy relationships (Quinn et al, 2019).…”
Section: Disentangling Digital Disempowermentmentioning
confidence: 99%